Penatalaksanaan Fisioterapi Pada Keterbatasan Lingkup Gerak Sendi Bahu Akibat Post Orif Fraktrus Haft Humerus Dextra (Management of Physiotherapy on Range of Motion Limitation due to Post Orif Fracture of Shaft Humerus Dextra) - Munzirin, Reni Mardika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
Beground: Fractures of the humerus is an interruption of the continuity condition of the upper arm bone tissue caused by collision or trauma directly or indirectly. Fractures can cause pain, swelling, spasms, decreased muscle strength and muscle wasting. Fractures of the humerus also resulted in limited range of motion (ROM) joint in the shoulder and elbow. The purpose of this study to determine whether there is an increase in the ROM on the right shoulder thathas limited the use of exercise therapy intervention in the form of passive and active exercise and hold relax. Research using case study method in one type of cases with a single sample, is given a dose of 6 times the treatment within 3 weeks. The result is an increase in ROM right shoulder evaluated using a goniometer, the comparison between T1 to T6 is S. 40⁰ -0⁰ -120⁰ became S. 50⁰ -0⁰ -140⁰, F. 100⁰ -0⁰ -60⁰ into F. 110⁰ -0⁰ -70⁰ and R do not become R. 75⁰ -0⁰ -80⁰.